Research on Educational Space Design for Preschool Children - Li, Hanqiao (Journal of Theory and Practice of Social Science, 2023)
Nowadays, children's education space has been recognized by many parents, which plays a very important role in the development of children. Children's physical and mental health development is closely related to their living and learning environment, which has an important impact on children's psychological development and character building in the process of growth. This paper analyzes the current situation of the design of preschool children's education space at home and abroad, summarizes the design strategy of preschool children's education space from the perspective of spatial theme positioning, color collocation and functional division, and carries out design practice in combination with specific projects. Finally, the design of the space and the concept of children's education fit each other, to design the education space suitable for children's study and life, so that children can grow and develop in a healthy and happy way.